2012
DOI: 10.1177/0954410012447767
|View full text |Cite
|
Sign up to set email alerts
|

Efficient use of an allotted airport annual noise budget through minimax optimization of runway allocations

Abstract: This article presents the development of a runway allocation planning tool that seeks to maximize the permissible number of flight operations into and out of an airport within a given annual noise budget. Although the model that underlies the planning tool is generic in nature, the tool has been customized for application to a specific airport, namely, Amsterdam airport Schiphol in the Netherlands. The noise budget regulations applicable at Schiphol stipulate limits on the annual cumulative noise loads at a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…In order to reduce noise impact caused by aircraft departure/arrival operations, noise abatement trajectory optimization has been applied to generate optimal trajectories, and a significant reduction in both the number of people affected by aircraft noise and fuel consumption has been reported (Zaporozhets and Tokare, 1998;Braakenburg et al, 2011;Hartjes et al, 2014Hartjes et al, , 2010Hartjes et al, , 2016Ho-Huu et al, 2017Hogenhuis et al, 2011;Prats et al, 2011Prats et al, , 2010bPrats et al, , 2010aSong et al, 2014;Torres et al, 2011;Visser andWijnen, 2003, 2001;Yu et al, 2016;Zhang et al, 2018). Furthermore, the development of allocation models to distribute aircraft movements over specific routes and runways have contributed to a significant reduction of aircraft noise effects (Chatelain and Van Vyve, 2018;Frair, 1984;Ganić et al, 2018;Ho-Huu et al, 2019a;Kuiper et al, 2012;Zachary et al, 2011Zachary et al, , 2010. In addition to the research on aircraft noise reduction, research on improving airport capacity and fuel consumption has been widely conducted (D'Ariano et al 2015;Sama et al 2017aSama et al , 2017bSama et al , 2018Sama et al , 2019.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to reduce noise impact caused by aircraft departure/arrival operations, noise abatement trajectory optimization has been applied to generate optimal trajectories, and a significant reduction in both the number of people affected by aircraft noise and fuel consumption has been reported (Zaporozhets and Tokare, 1998;Braakenburg et al, 2011;Hartjes et al, 2014Hartjes et al, , 2010Hartjes et al, , 2016Ho-Huu et al, 2017Hogenhuis et al, 2011;Prats et al, 2011Prats et al, , 2010bPrats et al, , 2010aSong et al, 2014;Torres et al, 2011;Visser andWijnen, 2003, 2001;Yu et al, 2016;Zhang et al, 2018). Furthermore, the development of allocation models to distribute aircraft movements over specific routes and runways have contributed to a significant reduction of aircraft noise effects (Chatelain and Van Vyve, 2018;Frair, 1984;Ganić et al, 2018;Ho-Huu et al, 2019a;Kuiper et al, 2012;Zachary et al, 2011Zachary et al, , 2010. In addition to the research on aircraft noise reduction, research on improving airport capacity and fuel consumption has been widely conducted (D'Ariano et al 2015;Sama et al 2017aSama et al , 2017bSama et al , 2018Sama et al , 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, research on the allocation of aircraft to current-in-use runways and routes can provide more realistic solutions, as reported in Refs. (Chatelain and Van Vyve, 2018;Frair, 1984;Ganić et al, 2018;Kuiper et al, 2012;Zachary et al, 2011Zachary et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, with the utilization of multi-objective optimization techniques, research has also demonstrated that the obtained optimal routes are beneficial not only from the noise perspective, but also in terms of fuel burn (Ho-Huu et al, 2017;Vinh Ho-Huu et al, 2018;Torres et al, 2011;Zhang et al, 2018). In addition to efforts invested to improve environmentally friendly departure and arrival routes, optimal distribution of aircraft and operational procedures to specific routes could also contribute significantly to environmental impact decrease (Frair, 1984;Heblij et al, 2007;Kuiper et al, 2013;Netjasov, 2008;Nibourg et al, 2012;Zachary et al, 2011Zachary et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of research on the allocation of flights to specific routes and runways, Frair (1984) developed an integer optimization model to find the optimal allocation of aircraft among available approach and departure routes with the aim of minimizing community annoyance. Kuiper et al (2012) maximized the number of aircraft movements operating at an airport within an allotted annual noise budget by optimally assigning annual flights to available routes and runways. Kim et al (2014) minimized airport surface emissions by concurrently allocating aircraft among runways and scheduling departure and arrival flights on these runways.…”
Section: Introductionmentioning
confidence: 99%